Assessing the role of village officials in social assistance delivery: Evidence on transparency and accountability from Situraja Village, Sumedang Regency - Atirista Nainggolan; Ellya Susilowati; Teta Riasih (LP2M Universitas Sarjanawiyata Tamansiswa, 2026)
Social assistance is a key component of the social protection system aimed at reducing poverty and protecting vulnerable groups. Its effectiveness depends largely on the role of village officials as local actors in community-based social protection. This study analyzes the role of village officials in implementing social assistance from the perspectives of transparency and accountability in Situraja Village, Sumedang Regency. A qualitative case study approach was employed involving 10 informants: four village officials, one SIKS-NG operator, one PKH facilitator, one social rehabilitation facilitator, one neighborhood head (RT), and three social assistance beneficiaries. Data were collected through in-depth interviews, observation, and document analysis. The findings reveal that the identification of prospective beneficiaries remains largely administrative and is not adequately supported by systematic data tracing and updating based on actual community conditions. Socialization has not been conducted in a structured or sustainable manner, leaving many beneficiaries without sufficient information regarding program objectives, eligibility criteria, implementation mechanisms, and their rights and obligations. Data verification and validation remain suboptimal due to the continued use of outdated data, limited field verification, and the absence of regular monitoring of changes in beneficiaries’ socio-economic conditions. Supervision is primarily focused on the distribution process rather than ensuring targeting accuracy. Consequently, transparency and accountability remain inadequate, as reflected in the persistence of inclusion and exclusion errors. The study recommends strengthening the capacity of village officials to improve transparent and accountable social assistance governance.